Tanshinone Ameliorates Glucocorticoid-Induced Bone Loss via Activation of AKT1 Signaling Pathway - Wang, Yanjun; Liu, Lin; Qu, Zechao; Wang, Dong; Huang, Wangli; Kong, Lingbo; Yan, Liang (Frontiers in Cell and Developmental Biology, 2022)
Purpose: Osteoporosis, a common disorder especially prevalent in the postmenopausal women and the elderly, is becoming a worldwide public health problem. Osteoporosis can cause severe joint pain, fragility fractures, and other symptoms, which can seriously impair the daily lives of affected patients. Currently, no gold-standard drug is available that can completely cure osteoporosis. Tanshinone is a traditional Chinese medicine, which can exhibit multiple biological activities. It might also display a protective effect on osteoporosis. However, the molecular mechanism through which tanshinone can improve osteoporosis remain unclear. The objective of our study is to explore the underlying mechanism behind the protective actions of tanshinone. Methods: The common KEGG pathways of tanshinone-targeted genes and osteoporosis were analyzed by using bioinformatics analysis. The bioinformatics analysis results were further validated both by in vitro and in vivo experiments. Results: 21 common KEGG pathways were identified between osteoporosis and tanshinone-targeted genes. It was further found that tanshinone could induce expression of AKT1, promote the proliferation of MSCs, and ultimately suppress their apoptosis. Conclusion: Taken together, our findings indicate that tanshinone can alleviate osteoporosis, its effect was potentially mediated through modulating AKT1 expression. Thus, tanshinone could serve as a promising treatment option for osteoporosis.